Lynda Barry : Girlhood through the Looking Glass - Kirtley, Susan E., 1972- (Book collections on Project MUSE., 2012)
Best known for her long-running comic strip 'Ernie Pook's Comeek', illustrated fiction, and graphic novels, the art of Lynda Barry has branched out to incorporate plays, paintings, radio commentary, and lectures, her oeuvre blurring the boundaries between fiction and memoir, comics and literary fiction, and fantasy and reality.'Lynda Barry' examines the artist's career and contributions to the field of comic art and beyond, concentrating specifically on Barry's recurring focus on figures of young girls, in a variety of mediums and genres.